Factors associated with healthcare services utilization among adults in rural communities of Benue State - Samuel, Gentle Kitoye; Ogar, Okpe (Faculty of Natural and Applied Sciences Journal of Health, Sports Science and Recreation, 2024)
This research looked at the variables that affect adults in rural Benue State communities' use of health care. To accomplish the study's goal, five research questions and five hypotheses were developed. The study's design was a questionnaire. In Benue State's rural settlements, 4,253,641 adults made up the study's population. A multistage sampling process was used to determine a sample size of 612 people. A self-structured questionnaire served as the data-collecting tool. Reliability coefficients for the questionnaire were 0.82 for knowledge of healthcare services, 0.91 for attitudes of healthcare personnel, 0.79 for distance to facilities, 0.78 for treatment costs, and 0.75 for cultural beliefs, in that order. The statistical software for social sciences was used for data analysis. The study questions and demographic data were analyzed using percentage and mean (x) sores, and the hypotheses were tested at the 0.05 level of significance using ANOVA. The study's conclusions showed that individuals had a high degree of healthcare service awareness (2.63). Utilization of healthcare services was also greatly influenced by variables such as the attitude of healthcare providers, accessibility to medical facilities, cost of care, and cultural attitudes. However, sociodemographic factors including location, age, marital status, and educational attainment are linked to the use of health services (>2.50), however, religion was not linked to the use of health care services (<2.50). It was concluded that the level of awareness and utilization of healthcare services among adults was high. Based on the findings, though the level of awareness found in this study was high, few of the respondents were also found not to be aware therefore, health professionals should sustain their efforts to promote awareness of healthcare services through different mass media.